Sexual harassment suffered by nursing professionals in healthcare instituitions (Research, Society and Development, 2021)
Objective: to identify in scientific publications the characteristics and outcomes of sexual harassment suffered by nursing professionals in health institutions. Method: Integrative review, carried out in June 2021. At first, 112 publications were identified in the databases. After applying the inclusion criteria, 23 articles were found, which were read in full. Exclusion criteria were applied, obtaining after careful analysis a sample of nine articles. Results: The most frequent victims were young women, single, and with little time of experience. Among those identified as perpetrators of sexual harassment, most were men, patients and/or family members, physicians, other nurses, and professionals who held leadership positions. Among the obstacles to not reporting are feelings of shame and embarrassment, disbelieving that there would be sanctions against harassers, and difficulties in reporting. Nurses showed high levels of stress, expressed sadness, and had disturbing memories about the moment of harassment. Conclusions: Given the above, it is necessary to encourage professionals and train them to be able to identify these situations, and act correctly reporting. In addition, it is necessary not to normalize the difficult situations that professionals often let go of because of their work.